2015
DOI: 10.1007/s10964-015-0311-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Effect of Depressive Symptoms on Prospective Alcohol Expectancies, Coping Motives, and Alcohol Outcomes in the First Year of College

Abstract: Problematic alcohol use and risk for dependence peak during late adolescence, particularly among first-year college students. Although students matriculating into college with depressive symptoms experience elevated risk for alcohol problems, few studies have examined the intervening mechanisms of risk. In this study, we examined depressed mood at college entry on prospective alcohol expectancies, drinking motives, and alcohol outcomes during the first year of college, adjusting for pre-college factors. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 72 publications
11
34
0
Order By: Relevance
“…Thus, internalizing characteristics’ relationship to trajectories of alcohol use/misuse differs from that of externalizing behaviors, the latter of which impact stages of alcohol use that precede the development of problems. This is well supported in the literature, as internalizing symptoms (including anxiety) are more often associated with more serious stages of alcohol outcomes, such as alcohol problems (Cooper, 1994, Kenney et al, 2015). Further research suggests that drinking to cope is more directly related to risky drinking than are negative moods (Cooper et al, 1995), and that this pathway may be more pronounced among women (Kenney et al, 2015).…”
Section: Discussionsupporting
confidence: 52%
“…Thus, internalizing characteristics’ relationship to trajectories of alcohol use/misuse differs from that of externalizing behaviors, the latter of which impact stages of alcohol use that precede the development of problems. This is well supported in the literature, as internalizing symptoms (including anxiety) are more often associated with more serious stages of alcohol outcomes, such as alcohol problems (Cooper, 1994, Kenney et al, 2015). Further research suggests that drinking to cope is more directly related to risky drinking than are negative moods (Cooper et al, 1995), and that this pathway may be more pronounced among women (Kenney et al, 2015).…”
Section: Discussionsupporting
confidence: 52%
“…Both cross-sectional (Gonzalez, Reynolds, & Skewes, 2011) and longitudinal findings (Kenney, Jones, & Barnett, 2015) suggest that drinking to cope motives are one mechanism through which depressive symptoms is associated with increased alcohol-related problems among college students. For example, Kenney, Jones, and Barnett (2015) found that for women, higher pre-college depressive symptoms predicted higher drinking to cope during college, which in turn was associated with more alcohol-related problems during college.…”
Section: Drinking To Cope Motivesmentioning
confidence: 99%
“…For example, Kenney, Jones, and Barnett (2015) found that for women, higher pre-college depressive symptoms predicted higher drinking to cope during college, which in turn was associated with more alcohol-related problems during college. As detailed above, research provides support for how depressive symptoms relate to alcohol-related problems among college students through drinking to cope motives.…”
Section: Drinking To Cope Motivesmentioning
confidence: 99%
“…During the period of adolescence, there is an identical model of alcohol use (frequency and amount), which, after that period, starts to vary depending on sex [9]. According to the study by Kenney et al [10], female adolescents use alcohol in smaller amounts than male adolescents do who consummate alcohol more frequently and in larger amounts, but this has not been explored enough.…”
Section: Introductionmentioning
confidence: 99%